Research on Metaphors in College English Teaching - Cao Haifeng; Sun Shuling; Lu Yaqin (Journal of Educational Issues, 2024)
Metaphor has not received the necessary attention in language learning and teaching because it has always been narrowly understood as a rhetorical device. The author of this article will provide a broad interpretation of metaphor, emphasizing that it is not only a rhetorical device, but also a way of thinking and an effective way to grasp the true meaning of language. Only after realizing the important role of metaphor in English teaching can teachers improve students’ metaphorical cognition and critical thinking abilities in their teaching practice, and consciously explore the true meaning and cultural background behind language. Therefore, only by making good use of metaphors can teachers effectively promote English teaching.